KAJIAN KOMPARATIF HUKUM JUAL BELI TANAH ANTARA INDONESIA DAN JERMAN: A Comparative Study of Land Sale and Purchase Law in Indonesia and Germany - Khansa Fatimah Sulistya; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2026)
Land has a strategic role in life, so it becomes an important aspect in ensuring certainty and legal protection for the community. Indonesia and Germany both regulate land trading as a form of transfer of land rights, but differences in the legal system influence the legal mechanisms, procedures, and powers of the process. Indonesia developed a national land law based on customary law with bright and cash characters, and implemented a land registration system that is a negative publication with a positive trend. In contrast, Germany adopted a system of strong codification of civil law through the Bürgerliches Gesetzbuch, which required notarial deeds and registration in Grundbuch as a constitutional requirement for birth and transfer of property rights to the land. The legal problems studied in this paper are found in the differences in the position and power of land registration law and its implications for legal certainty for rights holders. This study used a normative juridical method with a comparative approach to law through a library study of related laws, doctrines, and legal literature. The results and conclusion of the discussion show that land registration in Indonesia serves as a strong evidence but is not final, while in Germany land registration is a binding determinant of ownership and provides maximum legal protection. These differences directly affect the level of legal certainty in land buying and selling practices in both countries